Emanuel Hertz papers - Hertz, Emanuel, 1870-1940.; Hertz, Emanuel, 1870-1940.
Chiefly material relating to Hertz's work entitled Abraham Lincoln : A New Portrait (1931). Includes galley proofs of volume II, research material relating to the book, a catalog of the Herndon-Weik Collection of Lincolniana in the Library of Congress, articles and addresses relating to Lincoln, notes, notebooks, autographs, and autograph albums.
Lawyer, author, and collector of Lincolniana.
Collection material in English.
Keywords: Lincoln, Abraham, -- 1809-1865.; Herndon, William Henry, -- 1818-1891.; Weik, Jesse William, -- 1857-1930.; Autographs -- Collections; Authors; Collectors; Lawyers